Galeazzo Ciano : the fascist pretender - Hof, Tobias (Toronto ; Buffalo ; London : University of Toronto Press, 2021)
"Building on extensive archival research and important scholarly analysis, Galeazzo Ciano: The Fascist Pretender examines the life of Galeazzo Ciano, foreign minister of fascist Italy from 1936 to 1943 and Benito Mussolini's son-in-law. Ciano's life serves as the lens through which we gain a better understanding of crucial issues of Italian and European fascism, including the fascistization of society and politics, foreign relations, and the problem of succession. In order to accomplish this, the biography follows an innovative thematic structure that focuses on major aspects of Ciano's life, including his family, his political career, his diplomacy, and his desire to succeed Mussolini. Filling a substantial gap in the existing literature on the history of fascism, this is the first comprehensive analysis of a key player of Italian fascism other than Mussolini; it also offers a long overdue critical assessment of Ciano's famous diary, one of the most important texts from the period. Using visual materials such as photographs and films as sources and not just as illustrative material, Tobias Hof allows us to rethink our understanding of fascism and offers a new perspective on the history of fascist Italy."--
Frontmatter -- Contents -- Illustrations -- Acknowledgments -- Introduction -- 1. The Family -- 2. The Politician -- 3. The Diplomat -- 4. The Successor -- Epilogue: A Man of His Time -- Chronology -- Abbreviations -- Notes -- Bibliography -- Index
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on May 25, 2021).
JSTOR
Keywords: Ciano, Galeazzo, -- conte, -- 1903-1944.; Ciano, Galeazzo, -- conte, -- 1903-1944; Diplomats -- Italy -- Biography; Foreign ministers -- Italy -- Biography; Fascists -- Italy -- Biography; Fascism -- Italy -- History -- 20th century; Italy -- History -- 1922-1945.; Diplomates -- Italie -- Biographies; Ministres des affaires étrangères -- Italie -- Biographies; Fascistes -- Italie -- Biographies; Fascisme -- Italie -- Histoire -- 20e siècle.; Italie -- Histoire -- 1922-1945.; HISTORY / Europe / Italy; Diplomats; Fascism; Fascists; Foreign ministers; Italy; 1900-1999; Benito Mussolini; Galeazzo Ciano; Galeazzo Ciano's diaries; Italian fascism; Second World War; WWII; World War Two; biography; fascist oligarchy; international relations; twentieth-century Italian history; collective biographies; Biographies; History; Biographies; Biographies